Flow and heat transfer simulation analysis of 3D compact heat exchanger - G., Sashwin Nair; Oumer, A. N.; Azizuddin, Abd Aziz; Siregar, Januar Parlaungan (Akademi Baru, 2021)
One of the most common heat exchangers (HEs) utilized in the industry is a compact heat exchanger due to its superior advantage over other types of heat exchangers. Various geometric (fin spacing, tube inclination angle, etc) and process (such as flow velocity, temperature, etc) parameters affect the performance of such compact HEs. The objective of this paper is to investigate the effects of fin spacing, tube inclination angle, and airflow velocity for both tube configurations which are inline and staggered arrangements on heat transfer and pressure drop performance of fin-and-tube HEs. A three-dimensional (3D) numerical method with the aid of Ansys FLUENT software was carried out for the laminar flow condition. Based on the obtained results, the highest average heat transfer coefficient was observed at 120° for both tube arrangements while the lowest average pressure drop penalty is at 30°. Therefore, the recommended inclination angle when high heat transfer is needed is at 120° while if the pumping power is the major problem, 30 °or 150° is recommended.